“Get into the movies!”: the theme park’s relationship with post-classical Cinema - Dixon, Alexandra Elizabeth (2017)
This discussion examines the growing relationship between cinematic texts and the theme-park industry. Primarily focused on the post-classical period in Hollywood and its relationship to theme-park environments, this thesis analyses the evolution of the movie-based attraction from a passive retelling into an immersive and inclusive experience. The post-classical cinematic style, usually identified with the contemporary blockbuster movie, has its origins in the sensory experience of early cinema. I draw similarities between the two eras, emphasising the distinctiveness of a modern “cinema of attractions” that develops as films and theme-park rides become more closely intertwined. I elaborate the concepts of “immersion” and “inclusion” to describe and explain this process, identifying these as the distinguishing features of the evolving relationship between movies and theme-park attractions. Film-based attractions such as Back to the Future (1985), Star Wars (1977-2015) and Avatar (2009) exemplify how immersive and inclusive techniques are developed out of post-classical film aesthetics in order to enhance the affective experience of customers. Similarly, attraction-to-film adaptations, such as Disney’s Pirates of the Caribbean franchise (2003-present), combine immersion and inclusion with strategies of narrativization, incorporating film and attraction into a unified and self-referring storytelling world.